Refractive index change analysis in a high-power Yb-doped double-clad fiber laser - CARDOSO, ELBIS S. (2021)
An analytical investigation of the refractive index behavior of an ytterbium-doped optical fiber silica glass as a function of the core-clad temperature, upper-level population laser density, and pumping signal intensity is presented in this paper. For the substantiation of the investigation, three fundamental expressions were used, which describe the changes in the refractive index due to these physical phenomena in the laser medium. The model was evaluated considering a 500 W steady state fiber laser, operating in a two-end pumped configuration.